Drawing on Dialogues in Arts-Based Dynamic Interpersonal Therapy (ADIT) for Complex Depression: A Complex Intervention Development Study Using the Medical Research Council (UK) Phased Guidance - Havsteen-Franklin, Dominik; Oley, Mary; Sellors, Sarah Jane; Eagles, Diane (Frontiers in Psychology, 2021)
Aim: The aim of this paper is to present the development and evaluation of an art psychotherapy brief treatment method for complex depression for patients referred to mental health services. Background: Art Psychotherapy literature describes a range of processes of relational change through the use of arts focused and relationship focused interventions. Complex depression has a prevalence of 3% of the population in the West and it is recorded that in 2016 only 28% of that population were receiving psychological treatment. This study was developed to test the hypothesis of whether an accessible and acceptable approach to the treatment of complex depression could be developed in relation to existing evidence-based practice within mental health services. Method: The United Kingdom Medical Research Council phased guidance for complex intervention development was used (Phases I and II) to develop the intervention. The process included producing a literature overview, systematic description of clinical practice, including a logic model and a clinical protocol. The art psychotherapy protocol described an arts-based dynamic interpersonal therapy approach (ADIT), offered 1:1 over 24 sessions. Further to this the intervention was tested for referrer acceptability. The intervention is in the early stages of evaluation, using changes to the patient's depression and anxiety measured pre- and post-treatment with a follow-up measure at 3 months following completion of treatment. Results: Phase I of the study provided a good basis for developing a logic model and protocol. The authors found that there was good clinical consensus about the use of a structured clinical art psychotherapy method (ADIT) and the literature overview was used to support specific examples of good practice. The verification of clinical coherence was represented by a logic model and clinical protocol for delivering the intervention. The acceptability study demonstrated very high levels of acceptability for referrers reporting that (i) ADIT was acceptable for patients with complex/major depression, (ii) that they were likely to refer to ADIT in the future (iii) that the use of arts was likely to improve accessibility (iv) the use of arts was likely to improve outcomes and (v) that offering ADIT was an effective use of mental health resources. Discussion: Phase I of this intervention development study (following MRC guidance) demonstrated theoretical and practice coherence resulting in a clinical protocol and logic model. Whilst Phase II of this study showed promising results, Phase II would need to be sufficiently scaled up to a full trial to further test the intervention and protocol.